2011
DOI: 10.25035/ijare.05.01.04
|View full text |Cite
|
Sign up to set email alerts
|

Racing Start Safety: Head Depth and Head Speed During Competitive Swim Starts into a Water Depth of 2.29 m

Abstract: The head depths and head speeds of swimmers attained following the execution of racing starts during competition have not been well described. To address this, 211 competitive starts were filmed into a starting depth of 2.29 m with a block height of 0.76 m. Starts were stratified according to age, sex, stroke, and swim meet. Dependent measures were maximum depth of the center of the head, head speed at maximum head depth, and distance from the wall at maximum head depth. Significant main effects existed for ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
40
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 10 publications
(48 citation statements)
references
References 4 publications
7
40
1
Order By: Relevance
“…Once again, this is consistent with previous comparisons for "normal" and "shallow" starts (White et al, 2011). The increase in head speed at maximum head depth when swimmers are instructed to dive shallow is a logical outcome, as the head has traveled less distance through the water both vertically and horizontally and has therefore lost less momentum due to the drag forces of the water on the body (Cornett, White, Wright, Willmott, & Stager, 2011b).…”
Section: Head Speed At Maximum Head Depth and A Request To "Start Shasupporting
confidence: 89%
See 1 more Smart Citation
“…Once again, this is consistent with previous comparisons for "normal" and "shallow" starts (White et al, 2011). The increase in head speed at maximum head depth when swimmers are instructed to dive shallow is a logical outcome, as the head has traveled less distance through the water both vertically and horizontally and has therefore lost less momentum due to the drag forces of the water on the body (Cornett, White, Wright, Willmott, & Stager, 2011b).…”
Section: Head Speed At Maximum Head Depth and A Request To "Start Shasupporting
confidence: 89%
“…It is difficult to explain the exact nature of this relationship unless age is strongly associated with previous experience performing racing starts. Previously, Cornett et al (2011b) suggested that the head speed at maximum head depth attained by the swimmer is a likely to be a function of the size and skill of the athlete. While some fundamental movement skills differ in their age to maturity, these skills are reported to be capable of further refinement by experiential factors such as practice, encouragement, and instruction (Gallahue & Ozmun, 2006;Haywood & Getchell, 2009;Langendorfer & Roberton, 2002).…”
Section: The Effect Of Age On Racing Start Parametersmentioning
confidence: 99%
“…While it is certainly conceivable that a swimmer in this group could contact the pool bottom during the execution of a competitive backstroke start, from these data, this would appear to be unlikely. In terms of relative risk, given the greater depths attained during backstroke starts by the older swimmers, they appear to be at a greater relative risk than their younger counterparts as has been previously reported for forward starts from a block (Cornett et al, 2010(Cornett et al, , 2011.…”
Section: Maximum Depth Of the Center Of The Headsupporting
confidence: 56%
“…Statistical analysis revealed that head speed for racing starts from the standard (0.76 m) starting height and the pool deck both were significantly greater than for starts from an intermediate starting height (0.46 m) despite being deeper than those from the intermediate block height. This finding was unexpected as previous research had demonstrated that shallower racing starts are either consistent with greater head speed at maximum head depth (Cornett, White, Wright, Willmott, & Stager, 2011a;Cornett, White, Wright, Willmott, & Stager, 2011b;White, Cornett, Wright, Willmott, & Stager, 2011) or no difference in head speed at maximum head depth (Blitvich, McElroy, Blanksby, Clothier, & Pearson, 2000;Cornett, White, Wright, Willmott, & Stager, 2011c).…”
Section: Head Speed At Maximum Head Depthmentioning
confidence: 75%